Cyclic Voltammetric Study of Isoniazid - Rao, K.M.; Nageshwar Rao, P.; Adinarayana Reddy, K. (Asian Journal of Chemistry, 2010)
The electrochemical reduction behaviour of Isoniazid has been studied employing cyclic voltammetric technique in ethanol-water medium in a suitable pH range. The effect of solvent on the reduction of keto group is discussed. The kinetic parameters such as transfer coefficient and diffusion coefficient values have been evaluated. A possible reduction mechanism is proposed.